2022
DOI: 10.1177/09645284221125421
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of electroacupuncture for oxaliplatin-induced peripheral neuropathy in colorectal cancer patients: a single-blinded, randomized, sham-controlled trial

Abstract: Background: Oxaliplatin-based chemotherapy is a major first-line conventional therapy for advanced and metastatic colorectal cancer (CRC). However, oxaliplatin causes chemotherapy-induced peripheral neuropathy (CIPN). Acupuncture has long been used to alleviate limb numbness in Chinese medicine practice. Aim: The aim of this study was to examine the efficacy and safety of electroacupuncture (EA) for the alleviation of CIPN in CRC patients. Design: This was a pilot single-blinded, randomized, sham-controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Additionally, four studies used interventions pooled as ME [ 28 , 33 , 34 , 37 ], and 13 studies used interventions pooled as UCP. One three-arm trial [ 31 ] conducted a direct comparison of sensorimotor training (SMT), WBV, and UCP, two used cryotherapy [ 32 , 38 ], six used Acu [ 25 , 30 , 35 , 36 , 39 , 40 ] and one used ultrasound and multicomponent exercise (USME [ 34 ]). The close loop of the network map was formed by SMT, WBV, and UCP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, four studies used interventions pooled as ME [ 28 , 33 , 34 , 37 ], and 13 studies used interventions pooled as UCP. One three-arm trial [ 31 ] conducted a direct comparison of sensorimotor training (SMT), WBV, and UCP, two used cryotherapy [ 32 , 38 ], six used Acu [ 25 , 30 , 35 , 36 , 39 , 40 ] and one used ultrasound and multicomponent exercise (USME [ 34 ]). The close loop of the network map was formed by SMT, WBV, and UCP.…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis was performed by different scales. Among the studies, 15 applied the FACT/GOG-Ntx subscale for assessment [15,25,28,[30][31][32][33][34][35][36][37][38][39][40][41], involving 667 participants. A higher score of this subscale indicated more mild neuropathological symptoms.…”
Section: Peripheral Neuropathological Symptomsmentioning
confidence: 99%
“…Studies have shown that EA can improve postoperative pain in patients with esophageal cancer 288 and alleviate chemotherapy-induced peripheral neuropathy. [262][263][264] In a clinical trial of EA for chemotherapyinduced peripheral neuropathy, researchers established an EA group, a water bath group, a vitamin B1/B6 group, and a placebo group. The results showed no significant difference between the treatment group and the placebo group.…”
Section: Clinical Applications Of Electro-acupuncture In Cancer Therapymentioning
confidence: 99%
“…Furthermore, EA has been found to be effective in reducing pain caused by surgery or chemotherapy. Studies have shown that EA can improve postoperative pain in patients with esophageal cancer 288 and alleviate chemotherapy‐induced peripheral neuropathy 262–264 . In a clinical trial of EA for chemotherapy‐induced peripheral neuropathy, researchers established an EA group, a water bath group, a vitamin B1/B6 group, and a placebo group.…”
Section: Electro‐acupuncture In Cancer Therapymentioning
confidence: 99%
“…As a therapy of traditional Chinese medicine, acupuncture is widely used for palliative and supportive care for cancer patients, and evidence is increasing over the years ( 10 ). Some studies suggested that acupuncture might be effective for chemotherapy-induced neuropathic pain (CINP) ( 11 14 ). Based on the similar concept of acupuncture, acupuncture might have potential in the pain management of RRNP.…”
Section: Introductionmentioning
confidence: 99%